Chemical composition, seasonal variability and source identification of PM2.5 in an urban background site in Medellín—Colombia - Mauricio A. Correa-Ochoa; Miriam Gómez-Marín; Kelly Viviana Patiño-López; Luisa M. Gómez Pelaez; Santiago A. Franco (PLoS ONE, 2026)
This study assessed the chemical characterization of PM 2.5 at an urban background site in Medellín—Colombia, a city situated in a topographically constrained valley exposed to air pollution accumulation influenced by its complex Andean topography and a combination of local and regional emission sources. A total of 112 samples of PM 2.5 were collected between March 2019 and March 2020, samples went through comprehensive sampling and chemical characterization (ICP-MS for metals, ion chromatography for anions, thermal/optical analysis for carbonaceous species). Daily PM 2.5 concentrations ranged from 8.15 to 37.86 μ g/m 3 (mean: 21.73 ± 6.75 μ g/m 3 ). Principal Component Analysis (PCA) identified five major pollution sources, with mineral and resuspended dust (33.6% of explained variance) and secondary aerosols (17.0%) being the most prominent. The study area experiences clearly defined dry and wet periods, marked by distinct precipitation regimes. During the year these atmospheric conditions influence the concentration levels of pollutants. The integration of NOAA HYSPLIT back-trajectories and NASA FIRMS (VIIRS J2) fire hotspot data revealed long-range transport from the Magdalena, Orinoco and Amazon basins, deteriorating local air quality specially during dry periods. While local traffic and industrial emissions constitute a constant baseline, regional biomass burning and unfavorable meteorological conditions are the primary drivers of episodic high-pollution events. The study underscores the need for targeted strategies addressing both persistent sources as traffic or industrial emissions and episodic events to mitigate health and environmental impacts.